“From Spenser’s Proems in The Faerie Queene to Keats’s Introductions in Endymion” - Luisa Conti Camaiora (L'Analisi linguistica e letteraria, 2010)
The article documents and investigates the continual interest and appreciation of the Romantic poet, John Keats, for the work of the Renaissance poet, Edmund Spenser, and in particular, for the latter’s epic poem, The Faerie Queene. It is sustained that when Keats came to make his first attempt at a “long poem”, his poetic romance, Endymion, he kept particularly in mind Spenser’s six Proems, namely, the introductory parts to each of the six books that constitute the epic. The article analyzes the thematic contents as also the poetic and political motifs present in these Proems and it argues that Keats was strongly influenced by these elements in the composition of the four introductory sections of his Endymion. The comparison shows how, in these introductions, the presence of the Proems of The Faerie Queene explicates itself not only in the way Keats imitates and re-elaborates features present in Spenser but also in the way in which he assumes contrary and contrasting attitudes.